An Insight into Drug Repositioning for the Development of Novel Anti-Cancer Drugs - Bhattarai, Deepak; Singh, Sarbijt; Jang, Yerin; Hyeon Han, Seung; Lee, Kyeong; Choi, Yongseok (Current Topics in Medicinal Chemistry, 2016)
Increased investments and development of new technologies in drug discovery have barely improved the outcome of medicinal entities in the drug discovery market from a long time. Minimal success rates of drug approvals, poor safety profiles, and long development processes are some of many hurdles encountered in the drug discovery field. Therefore, drug repurposing can provide an alternative approach to meet the demands of the new, potent and safe anti-cancer agents in terms of both economic cost and time efficiency. The common molecular pathways of different diseases and secondary indications of most of the approved drugs, and advances in genomics, informatics and biology, as well as the availability of approved or safe drug libraries can certainly provide an improved and efficient way of screening safer drugs for new indications. Promising results of drug repurposing in different therapeutic areas have encouraged the scientific community to discover new drugs for different diseases using this methodology. Herein, we provide a general overview of structurally and functionally diverse approved drugs that have been repurposed as anti-cancer drugs.
Keywords: Safety